346. Eastern Equine Encephalitis and Use of Intravenous Immunoglobulin Therapy and High-Dose Steroids. (31st December 2020) - Collens, Sarah I; Wilcox, Douglas R; Mukerji, Shibani; Mateen, Farrah J; Solomon, Isaac H
Abstract: Background: Eastern equine encephalitis (EEE) is a mosquito-borne viral infection with significant neurological morbidity and mortality. The clinical presentation and patient outcomes after treatment with IVIG, high-dose steroids, or standard of care alone in EEE remains unclear. Methods: A retrospective observational study of patients admitted to two tertiary academic medical centers in Boston, Massachusetts with EEE from 2005 to 2019. Results: Of 17 patients (mean [SD] age, 50 [26] years; 10 (59%) male, and 16 (94%) White race), 17 patients had fever (100%), 15 had encephalopathy (88%), and 12 had headache (71%). Eleven of 14 patients with cerebrospinal fluid (CSF) cell count differential had a neutrophil predominance (mean [SD], 60.6% of white blood cells [22.8]) with an elevated protein level (mean [SD], 112 mg/dL [48.8]). Affected neuroanatomical regions included the basal ganglia (n=9/17), thalamus (n=7/17), and mesial temporal lobe (n=7/17). A total of 11 patients (65%) received IVIG; 8 (47%) received steroids. Of the patients who received IVIG, increased time from hospital admission to IVIG administration correlated with worse long-term disability as assessed by modified Rankin Score (mRS) (r=0.72, p=0.02); steroid use was not associated with mRS score. The mortality was 12%. Figure 1. Imaging Characteristics: Typical Pattern of MRI Involvement and Affected Neuroanatomical Regions in Patients with Eastern Equine Encephalitis. All images displayed are the T2-FLAIR sequence. (A) Representative images of pattern of typical neuroanatomical region involved in one patient with demonstrated involvement of the temporal lobe and pons, temporal lobe and midbrain, and basal gangial by T2-FLAIR hyperintensity (panels left to right). (B) Representative images of patients with mild (mRS 0–2), moderate (mRS 3–4), and severe (mRS 5–6) disability score at discharge. (C) Representative images of one patient over course of hospitalization at days 1, 4, and 10 after admission. (D) Quantification of neuroanatomical region involvement in initial MRI of patients with EEE as determined by T2-FLAIR hyperintensity. An area was scored as abnormal only once per patient. Figure 2. Outcomes in Patients with Eastern Equine Encephalitis. Patient disability by modified Rankin Score (mRS) of EEE patients at admission to the hospital, discharge from the hospital, and last recorded follow-up (A). Time to IVIG administration compared to mRS at discharge (B), and most recent clinical follow-up (C). Table 1. Demographics, Clinical Characteristics, and Laboratory Data in Patients with Eastern Equine Encephalitis. Abbreviations: CSF = cerebrospinal fluid, WBC = white clood count, EEG = electroencephalogram, ALT = alanine aminotransferase, AST = aspartate transaminase. Demographic data was collected for all patients with confirmed EEE. Altered mental status included any description of encephalopathy, confusion, or difficulty with attention. Seizures were defined as clinical events with a high-degree of suspicion to be true seizures, and were entirely comprised of generalized tonic-clonic seizures. Conclusion: Clinicians should suspect EEE in immunocompetent patients with early subcortical neuroimaging abnormalities and CSF neutrophilic predominance. This study suggests a lower mortality than previously reported, but a high morbidity rate in EEE. IVIG as an adjunctive to standard of care may be considered early during hospitalization. Disclosures: All Authors : No reported disclosures